1986
DOI: 10.1016/s0006-3495(86)83692-x
|View full text |Cite
|
Sign up to set email alerts
|

Early Picosecond Events in the Photocycle of Bacteriorhodopsin

Abstract: The primary processes of the photochemical cycle of light-adapted bacteriorhodopsin (BR) were studied by various experimental techniques with a time resolution of 5 x 10(-13) s. The following results were obtained. (a) After optical excitation the first excited singlet state S(1) of bacteriorhodopsin is observed via its fluorescence and absorption properties. The population of the excited singlet state decays with a lifetime tau(1) of approximately 0.7 ps (430 +/- 50 fs) (52). (b) With the same time constant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
167
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(184 citation statements)
references
References 32 publications
17
167
0
Order By: Relevance
“…1c). The resulting fluorescence quantum yield of pSRII is calculated to 1.2 ϫ 10 -4 , which is very close to the value of BR (1.3 ϫ 10 -4 ), which in turn is in good agreement with earlier publications (13). Estimation of excited-state lifetimes using ref.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…1c). The resulting fluorescence quantum yield of pSRII is calculated to 1.2 ϫ 10 -4 , which is very close to the value of BR (1.3 ϫ 10 -4 ), which in turn is in good agreement with earlier publications (13). Estimation of excited-state lifetimes using ref.…”
Section: Resultssupporting
confidence: 88%
“…In BR the kinetics at 490 nm (excited-state absorption) and 900 nm (stimulated emission) were used to assign the 500-fs transient to the transition to the first ground-state product J (13,31). Because sSRI has similar absorption properties as BR, the 490-nm absorption transient can be taken as an indication that both processes, the 5-ps and the 33-ps process, are related to the S 1 decay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The I1 intermediate shows an overall blue shift of the difference spectrum compared with the excited state, along with a significant loss in signal. This difference spectrum represents a red shift of the absorbance of Rh-Bl, similar to that observed for J and K intermediates in bacteriorhodopsin (BR) (23). The final P560 intermediate is formed from I1 within 400 ps along with a blue shift, an increase in negative contributions, and an increase but no spectral shift in the induced absorption.…”
Section: Localization Of Hkr1 In the Eyespot Of Chlamydomonas-assupporting
confidence: 70%
“…3, which show a spectrally silent deprotonated species before protonation occurs in 2.3 ms. The excited state lifetimes of 5 and 60 ps are unusually long for a rhodopsin (22,23). A study on unprotonated Schiff base model compounds showed that decreasing the polarity of the environment strongly increases the excited state lifetime (24).…”
Section: Localization Of Hkr1 In the Eyespot Of Chlamydomonas-asmentioning
confidence: 99%